D-Methionine Ameliorates Cisplatin-Induced Muscle Atrophy via Inhibition of Muscle Degradation Pathway. (February 2019) - Wu, Ching-Te; Liao, Jiuan-Miaw; Ko, Jiunn-Liang; Lee, Yao-Ling; Chang, Hui-Yi; Wu, Cheng-Hsi; Ou, Chu-Chyn
Cisplatin induces anorexia, weight loss, loss of adipose tissue, skeletal muscle atrophy, and serious adverse effects that can cause premature termination of chemotherapy. The aim of this study was to use an animal model to assess cisplatin therapy (3 cycles) with and withoutd -methionine to investigate its protective effects on cisplatin-induced anorexia and skeletal muscle wasting. Wistar rats were divided into 3 groups and treated as follows: saline as control (group 1), intraperitoneal cisplatin once a week for 3 weeks (group 2), and intraperitoneal cisplatin once a week for 3 weeks plus oral administration ofd -methionine (group 3). Tissue somatic index (TSI), gastric emptying index (GEI), and feeding efficiency were measured. Both hepatic lipid metabolism and muscle atrophy-related gene expressions and C2C12 myotubes were determined by polymerase chain reaction. Micro–computed tomography (micro-CT) was used to conduct assessment of bone microarchitecture indices. Pathological changes of the gastric mucosa were assessed by hematoxylin and eosin staining after euthanizing the animals.d -Methionine increased food intake, weight gain, gastric emptying, and feeding efficiency, as well as decrease stomach contents, after cisplatin injections. Cisplatin caused shortening of myofibers. Cisplatin-induced muscle mass wasting was mediated by the elevation of mRNA expressions of MAFbx and MuRF-1 in ubiquitin ligases in muscle tissue homogenate. The mRNA expressions of MyoD and myogenin, markers of muscle differentiation, declined following cisplatin administration. The administration ofd -methionine not only led to significant improvements in myofiber diameter and cross-sectional fiber areas but also reversed muscle atrophy-related gene expression. However, there were no significant changes in stomach histology or microarchitecture of trabecular bone among the study groups. The results indicate thatd -methionine has an appetite-enhancing effect and ameliorates cisplatin-induced adipose and muscle tissue loss during cisplatin-based chemotherapy.